Irradiation asymmetry effects on the direct drive targets compression for the megajoule laser facility. (24th July 2015) - Demchenko, N.N.; Doskoch, I.YA.; Gus'kov, S.YU.; Kuchugov, P.A.; Rozanov, V.B.; Stepanov, R.V.; Vergunova, G.A.; Yakhin, R.A.; Zmitrenko, N.V.
Abstract: In the previous works (Rozanov et al ., 2013; 2015) we have performed one-dimensional (1D) numerical simulations of the target compression and burning at the absorbed energy of ~1.5 MJ. As a result, the target was chosen to have a low initial aspect ratio in order to be less sensitive to the influence of such parameters as laser pulse duration, total laser energy, and equations of state model. The simulation results demonstrated a higher probability of ignition and effective burning of such a system. In the present work we discuss the impact of irradiation asymmetry on this baseline target implosion. The details of the 1D compression and a possible influence of 2D and 3D effects due to the hydrodynamic instability and mixing have been described. In accordance with the 2D calculations the target is still ignited, however, the symmetry analysis of 3D ones gives reasons to further reduce the efficiency of conversion of kinetic energy into potential energy.